Pengaruh Digital Content Marketing Terhadap Loyalitas Pelanggan Melalui Behavioral Engagement, Brand Trust, Brand Attachment Pada Generasi Z - Ernawan Dwi Hanartyo; Indah Nurhasan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the effect of digital content marketing on customer loyalty by considering the mediating roles of behavioral engagement, brand attachment, and brand trust among Generation Z consumers. This research employs a quantitative approach using Structural Equation Modelling based on Partial Least Squares (SEM-PLS). Data were collected through questionnaires distributed to Generation Z respondents who actively use social media. The results indicate that digital content marketing has a positive and significant effect on behavioral engagement, brand attachment, and brand trust, but does not have a significant direct effect on customer loyalty. Instead, customer loyalty is formed indirectly through mediating mechanisms. Behavioral engagement significantly influences brand attachment, brand trust, and customer loyalty. Furthermore, brand attachment has a significant effect on brand trust and customer loyalty, while brand trust also significantly affects customer loyalty. These findings suggest that customer loyalty among Generation Z is not formed directly through exposure to digital content, but rather through a gradual process involving active engagement, emotional attachment, and trust in the brand. Therefore, an effective digital content marketing strategy should focus on encouraging consumer interaction, building emotional connections, and enhancing brand credibility in order to achieve sustainable customer loyalty.